Phytochemicals from Calophyllum macrocarpum Hook.f. and its cytotoxic activities. Issue 2 (17th January 2022) - Karunakaran, Thiruventhan; Firouz, Noor Syarafana; Santhanam, Rameshkumar; Jong, Vivien Yi Mian
Abstract: Species from the Genus Calophyllum are rich source for bioactive phenolic compounds such as coumarins and xanthones. Phytochemical study carried out on the plant, Calophyllum macrocarpum has led to the isolation of three known prenylated xanthones, ananixanthone (1 ), trapezifolixanthone (2 ) and 8-deoxygartanin (3 ) with two common triterpenoids, stigmasterol (4 ), and friedelin (5 ). The structures of these compounds were identified and determined using spectroscopic techniques such as NMR and MS. The cytotoxic activities of compounds 1 and 2 as well as the extracts were tested against HeLa Chang liver and HEK-293 cell lines. Compound 1 exhibited appreciable cytotoxicity with the IC50 value of 11.08 ± 3.09 µM against HeLa Chang liver cell line and moderate cytotoxicity against HEK-293 cell line while compound 2 showed limited toxicity against these two cell lines. Graphical Abstract: UF0001